Effect of precipitation on synthetic aperture radar hurricane wind field retrieval - Guo, Chaogang; Ai, Weihua; Hu, Shensen; Du, Xiaoyong; Chen, Nan (Frontiers in Environmental Science, 2022)
C-band synthetic aperture radar (SAR) with all-weather observation capability is gradually being used for the high-resolution observation of tropical cyclones (TCs). The extreme wind speed in TCs is retrieved by combining the co- and cross-polarized SAR signals. However, the heavy precipitation associated with TCs will seriously affect the retrieval of SAR sea surface wind speed. In this study, the effects of precipitation-related parameters and phenomena on wind speed retrieval under strong TC conditions were examined by using the data from co-located global precipitation measurement Dual-frequency Precipitation Radar, SAR on Sentinel-1 and Radarsat-2, and stepped frequency microwave radiometer. The results show that precipitation will increase the retrieval error of wind speed, and the effect of convective precipitation is more obvious than that of stratiform precipitation. When the wind speed is less than 30 m/s and the rain rate is less than 20 mm/h, the distribution of the melting layer has no obvious effect on SAR wind speed retrieval. Rain cells are mainly the product of convective precipitation and can also be produced when the storm top height is very low. An increase in the vertical-horizontal (VH) polarized normalized radar cross section (NRCS) in rain cells is usually greater than that of the vertical-vertical (VV) polarized NRCS because the sensitivity of the VH signal in a hurricane area is usually greater than that of the VV signal. When the rain rate is low, the difference between the retrieved wind speed inside and outside the rain cells is within the error range of hurricane wind speed retrieval. When the rain rate is further increased, the difference will exceed 10 m/s.